THE EFFECT OF CAPITAL STRUCTURE, FIRM GROWTH, FIRM SIZE AND PROFITABILITY ON FIRM VALUE OF COMPANIES WITH GOOD CORPORATE GOVERNANCE AS A MODERATING VARIABLES IN MANUFACTURING COMPANIES IN THE BASIC AND CHEMICAL INDUSTRY REGISTERED IN INDONESIA STOCK EXCHANGE - Tumanggor, Arief Hidayat (Asosiasi Dosen Akuntansi Indonesia, 2019)
the objective of this study is to determine the effect of capital structure, firm growth, firm size and profitability on the value of manufacturing companies in the Basic Industry and Chemical sectors listed on the Indonesia Stock Exchange. The independent variables in this study are capital structure, firm growth, firm size and profitability. The dependent variable is firm value. The moderating variable is Good Corporate Governance. This type of research is a causal associative research conducted to determine the effect or also the relationship between two or more variables. This study looked at manufacturing companies listed on the Indonesia Stock Exchange in 2013-2017. The sample in this study was 29 companies so the number of observations in this study was 29x5 = 145 data. The sampling technique used was purposive sampling. The analytical method used is panel data regression analysis and moderating testing with the help of Eviews software. The results of this study indicate that simultaneously capital structure, firm growth, firm size and profitability affect firm value. While partially the capital structure does not affect firm value, firm growth affects firm value, firm size affects firm value and profitability affects firm value. While testing moderating good corporate governance has no effect on capital structure, firm growth, firm size, profitability and firm value.